Impacts of Recreational Use on Soil Dynamics in Kastamonu Urban Forest - Baç, Beyza; Güneş Şen, Senem (Kastamonu University, 2025)
This study assessed the effects of recreational use intensity on soil compaction and key physical and chemical soil properties in the Kastamonu Urban Forest, Turkey. Soil penetration resistance, bulk density, organic matter pH, electrical conductivity, and soil texture were measured across three land-use types (forest, recreation area, path) at two depths (0–10 cm and 10–20 cm). Results revealed that increasing use intensity significantly elevated soil penetration resistance and bulk density values, while organic matter decreased, particularly in path and recreation areas. Forest soils consistently showed the lowest soil penetration resistance (1.18–1.48 MPa) and bulk density (0.86–0.93 g/cm³) and the highest organic matter (9–12.4%), highlighting their protective role. In contrast, path soils exhibited the highest soil penetration resistance (up to 3.7 MPa), bulk density (1.60 g/cm³), and electrical conductivity (203–205 µS/cm), indicating greater compaction and reduced soil quality. Soil pH ranged from acidic in forest areas (5.5–5.9) to near-neutral in high-use areas. Correlation analyses confirmed strong links between increased compaction and reduced organic matter, along with changes in pH and electrical conductivity. Soil texture differences, with higher sand content in intensively used areas, further contributed to compaction. These findings underscore the critical role of forested areas in maintaining soil health and highlight the need for sustainable management practices to reduce compaction in urban forests. This research contributes to understanding human impacts on urban forest soils and informs strategies to balance recreation and ecosystem conservation.
Keywords: Natural Resource Management; Soil Pollution and Control; Doğal Kaynak Yönetimi; Toprak Kirliliği ve Kontrolü; Toprak sıkışması; kent orman; rekreasyonel kullanım; toprak özellikleri; Kastamonu; Soil compaction; urban forest; recreational use; soil properties; Kastamonu